Effectiveness of oxygen nebulization at preventing radiotherapy-induced mucositis in patients with nasopharyngeal cancer - Juan Xu; Rong Yan; Pei-Ying Zhuo; Ran-Ran Li; Hong-Xia Ge; Wen-Fang Lu (Elsevier, 2014)
Purpose: To evaluate the effectiveness of oxygen nebulization at preventing radiotherapy-induced mucositis in patients with nasopharyngeal cancer. Methods: Sixty patients with nasopharyngeal cancer treated with simultaneous integrated boost intensity-modulated radiotherapy were randomly assigned to oxygen nebulization or ultrasonic nebulization groups; treatment was once daily for 20 minutes. All patients received routine oral care. We compared saliva pH and volume, food intake, and change in oral mucosa during radiotherapy, and dry mouth and sore throat after radiotherapy between the two groups. Results: There were significant differences in the incidence of grade III or IV mucositis, saliva volume and pH, and dry mouth and sore throat between the two groups when the total dose was 33 Gy (p < 0.05 or p < 0.01). Conclusion: Oxygen nebulization reduces radiotherapy-induced mucositis and relieves symptoms such as dry mouth and sore throat in patients with nasopharyngeal cancer.